Spatial–temporal patterns in Mediterranean carnivore road casualties: Consequences for mitigation - Grilo, Clara; Bissonette, John a.; Santos-Reis, Margarida (Biological Conservation, 2009)
Many carnivores have been seriously impacted by the expansion of transportation systems and networks; however we know little about carnivore response to the extent and magnitude of road mortality, or which age classes may be disproportionately impacted. Recent research has demonstrated that wildlife–vehicle-collisions (WVC) involving carnivores are modulated by temporal and spatial factors. Thus, we investigated road mortality on a guild of small and medium-sized carnivores in southern Portugal using road-kill data obtained from a systematic 36 months monitoring period along highways (260 km) and national roads (314 km) by addressing the following questions: (a) which species and age class are most vulnerable to WVC? (b) are there temporal and/or spatial patterns in roadkill? and (c) which life-history and/or spatial factors inﬂuence the likelihood of collisions? We recorded a total of 806 carnivore casualties, which represented an average of 47 ind./ 100 km/year. Red fox and stone marten had the highest mortality rates. Our ﬁndings highlight three key messages: (1) the majority of road-killed individuals were adults of common species; (2) all carnivores, except genets, were more vulnerable during speciﬁc life-history phenological periods: higher casualties were observed when red fox and stone marten were provisioning young, Eurasian badger casualties occurred more frequently during dispersal, and higher Egyptian mongoose mortality occurred during the breeding period; and (3) modeling demonstrated that favorable habitat, curves in the road, and low human disturbance were major contributors to the deadliest road segments. Red fox carcasses were more likely to be found on road sections with passages distant from urban areas. Conversely, stone marten mortalities were found more often on national roads with high of cork oak woodland cover; Egyptian mongoose and genet road-kills were found more often on road segments close to curves. Based on our results, two key mitigation measures should help to reduce WVC in Portugal. The ﬁrst involves the improvement of existing crossings with buried and small mesh size fence to guide the individuals towards to the passages, in road segments with high trafﬁc volume (>1200 vehicles/night) and located in preferred carnivore habitats. The second mitigation involves cutting or removal of dense vegetation in verges of road segments with curves to aid motorists in seeing animals about to cross.
Keywords: Meso-carnivores; Mitigation; Modeling; Road ecology; Road-kill patterns; ‘‘Montado’’ lands